2001
DOI: 10.1074/jbc.m104709200
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase II-dependent Positional Effects on mRNA 3′ End Processing in the Adenovirus Major Late Transcription Unit

Abstract: During the early phase of adenovirus infection, the promoter-proximal L1 poly(A) site in the major late transcription unit is used preferentially despite the fact that the distal L3 poly(A) site is stronger (i.e. it competes better for processing factors and is cleaved at a faster rate, in vitro). Previous work had established that this was due at least in part to the stable binding of the processing factor, cleavage and polyadenylation specificity factor, to the L1 poly(A) site as mediated by specific regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Although the present study has a number of features in common with previous studies on the coupling of 3 0 end processing to transcription, it is difficult to make direct comparisons. For example, like us, Mifflin and Kellems (1991) observed processing that was fast and efficient when coupled to transcription, and Yonaha and Proudfoot (1999; and Ahuja et al (2001) observed functional interactions between processing and transcription. Nevertheless, it is not possible to say if a tether requirement would have been evident in those studies, because they all employed crowding agents like PVA to enhance the processing.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although the present study has a number of features in common with previous studies on the coupling of 3 0 end processing to transcription, it is difficult to make direct comparisons. For example, like us, Mifflin and Kellems (1991) observed processing that was fast and efficient when coupled to transcription, and Yonaha and Proudfoot (1999; and Ahuja et al (2001) observed functional interactions between processing and transcription. Nevertheless, it is not possible to say if a tether requirement would have been evident in those studies, because they all employed crowding agents like PVA to enhance the processing.…”
Section: Discussionmentioning
confidence: 66%
“…Very likely, newly extruded RNA is packaged in a way that makes it a preferred substrate for the next step of mRNA production, but this is really coupling in the broader precursor-product sense. For this reason, studies directed at functional coupling often compare the processing of RNA produced by RNA polymerase II with the processing of RNA produced by T7 RNA polymerase under the same conditions (Mifflin and Kellems, 1991;Ahuja et al, 2001). However, even here caution is required because, as discussed earlier, mere involvement of the polymerase as a participant in the processing reaction is not synonymous with functionally coupling processing to transcription.…”
Section: Discussionmentioning
confidence: 99%
“…For example, serine-rich proteins within the cell have been shown to suppress viral infection by blocking the obligate splicing of adenoviral pre-mRNA (15). Furthermore, the decrease in adenoviral replication may be due to ineffective or absent cleavage of polyadenylated RNA (16). In both of these cases, specific factors expressed by the cells may influence the outcome of productive infection.…”
Section: Discussionmentioning
confidence: 99%